Komunikasi Krisis: Kunci Hubungan dan Ketahanan Organisasi - Vincentia Stephani; Farikha Rachmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The media industry today faces significant challenges in managing internal communication, especially during crises. Effective communication is crucial to maintaining stability and ensuring the continuity of organizational operations. This study aims to examine the influence of organizational employee relationship and organizational resilience restoration on internal crisis communication in media companies in Surabaya. A total of 116 respondents were selected using a non-probability sampling technique, specifically purposive sampling. Data were collected through questionnaires and interviews, with the questionnaire results analyzed using Smart PLS 3.0. The findings indicate that both organizational employee relationship and organizational resilience restoration significantly influence internal crisis communication in media companies in Surabaya.